Diagnosis and treatment of multiple myeloma in Germany: analysis of a nationwide multi-institutional survey - Merz, Maximilian; Goldschmidt, Hartmut (Annals of hematology, 2017)
A nationwide, multi-institutional survey was performed in 2011 and 2015 to analyze routine practice for myeloma patients outside clinical trials in Germany. We contacted university hospitals, community hospitals, and office-based hematologists in order to enter clinical data from newly diagnosed and relapsed patients into an online platform. Complete datasets were available for 478 (2011) and 515 (2015) patients. While median age at diagnosis increased from 70 to 72 years, patients had fewer concomitant diseases (2011 61%; 2015 51%) and presented with equal performance status (ECOG 0-1, 2011 66%; 2015 68%). Cytogenetic analysis was performed in 53% (2011) and 59% (2015). Patients ≥70 years, or patients with comorbidities who were no candidates for autologous transplantation (ASCT), were less frequently tested for cytogenetic abnormalities (p = 0.001, respectively). There were more candidates for ASCT ≥65 years in 2015 (57%) than in 2011 (27%). Bortezomib was used in 92% of transplant-eligible and 66% of transplant-ineligible patients as frontline therapy in 2015. Application of bortezomib and lenalidomide for the first relapse changed from 2011 (bortezomib 45%; lenalidomide 27%) to 2015 (bortezomib 28%; lenalidomide 54%). For the second relapse, application of lenalidomide decreased from 2011 (36%) to 2015 (23%). Pomalidomide entered treatment for the second relapse in 2015 (11% of patients). Taken together, we demonstrate that results from clinical trials are implemented into general practice in Germany.